2021
DOI: 10.1016/j.asmr.2021.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Testing of Suture Anchor Versus Transosseous Tunnel Technique for Quadriceps Tendon Repair Yields Similar Outcomes: A Systematic Review

Abstract: Purpose: To systematically review the literature to evaluate the biomechanical properties of the suture anchor (SA) versus transosseous tunnel (TO) techniques for quadriceps tendon (QT) repair. Methods: A systematic review was performed by searching PubMed, the Cochrane Library, and Embase using PRISMA guidelines to identify studies that evaluated the biomechanical properties of SA and TO techniques for repair of a ruptured QT. The search phrase used was "quadriceps tendon repair biomechanics". Evaluated prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Numerous cadaveric biomechanical studies have shown the superiority of the single or double anchor method. Apart from the limited number of cases in our study, the use of double row anchors in the treatment of acute quadricipital tendon ruptures seems to be an attractive technique with excellent medium-term results noted in our study, so a larger sample with consequent hindsight will make it possible to confirm the place of this technique in this pathology [1] , [4] , [8] , [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 68%
“…Numerous cadaveric biomechanical studies have shown the superiority of the single or double anchor method. Apart from the limited number of cases in our study, the use of double row anchors in the treatment of acute quadricipital tendon ruptures seems to be an attractive technique with excellent medium-term results noted in our study, so a larger sample with consequent hindsight will make it possible to confirm the place of this technique in this pathology [1] , [4] , [8] , [12] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 68%
“…When compared with constructs repaired by the TT technique, tendon displacement on initial cycling is consistently lower for SA fixation constructs, according to a systematic review. 18 Between the SA and TT groups, no significant differences in construct stiffness or modes of failure were observed. Regarding modes of failure, knot slippage was the most common mode for both the TT and SA techniques.…”
Section: Discussionmentioning
confidence: 89%
“…The modes of failure in the TT group were knot slippage (38.7%), suture tearing through tendon (32.3%), and suture breakage at knots (29.0%). 18 …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on biomechanical comparison studies of both techniques reported similar ultimate load to failure and final displacement. 46 However, another recent systematic review reported smaller gap formations after both quadriceps and PT ruptures in suture anchor fixation compared with transosseous tunnel technique. 47 Mehta et al reported improved ROM and lower complication rates for transosseous tunnel technique, and similar Lysholm scores and re-rupture rates in a systematic review.…”
Section: Discussionmentioning
confidence: 96%